Benthic Carbon Remineralization and Iron Cycling in Relation to Sea Ice Cover Along the Eastern Continental Shelf of the Antarctic Peninsula - Baloza, M.; Henkel, S.; Geibert, W.; Kasten, S.; Holtappels, M.; Henkel, S.; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany; Geibert, W.; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany; Kasten, S.; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany; Holtappels, M.; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany (Journal of Geophysical Research: Oceans, 2022)
Rapid and profound climatic and environmental changes have been predicted for the Antarctic Peninsula with so far unknown impact on the biogeochemistry of the continental shelves. In this study, we investigate benthic carbon sedimentation, remineralization and iron cycling using sediment cores retrieved on a 400 mile transect with contrasting sea ice conditions along the eastern shelf of the Antarctic Peninsula. Sediments at comparable water depths of 330–450 m showed sedimentation and remineralization rates of organic carbon, ranging from 2.5 to 13 and 1.8–7.2 mmol C m−2 d−1, respectively. Both rates were positively correlated with the occurrence of marginal sea ice conditions (5%–35% ice cover) along the transect, suggesting a favorable influence of the corresponding light regime and water column stratification on algae growth and sedimentation rates. From south to north, the burial efficiency of organic carbon decreased from 58% to 27%, while bottom water temperatures increased from −1.9 to −0.1°C. Net iron reduction rates, as estimated from pore‐water profiles of dissolved iron, were significantly correlated with carbon degradation rates and contributed 0.7%–1.2% to the total organic carbon remineralization. Tightly coupled phosphate‐iron recycling was indicated by significant covariation of dissolved iron and phosphate concentrations, which almost consistently exhibited P/Fe flux ratios of 0.26. Iron efflux into bottom waters of 0.6–4.5 μmol Fe m−2 d−1 was estimated from an empirical model. Despite the deep shelf waters, a clear bentho‐pelagic coupling is indicated, shaped by the extent and duration of marginal sea ice conditions during summer, and likely to be affected by future climate change. Plain Language Summary: The seafloor of the shallow shelf seas plays a significant role in the recycling of organic carbon and acts as a nutrient source for algae growth in the upper water layers. In Antarctic waters, the change in sea ice cover has a great impact on the growth of algae and the subsequent sinking ...